RFID Systems as Data Supplier of SCEM-Systems - (:unkn) unknown (GITO-VERLAG, 2008)
Because interruptions in supply chains compromise the efficiency of these chains it is important to identify them rapidly as well as to react on them correctly. Supply Chain Event Management Systems (SCEM-Systems) support these identification and reaction functions. As a real-time data supplier of SCEM-Systems RFID Systems increase the quality of the collected data that directly influences the efficiency of SCEM-Systems.
Keywords: Supply Chain Event Management Systems; RFID Systems; Data Quality